Crystallographic and magnetic properties of manganese ferrites prepared by liquid nitrogen quenching - Sunghyun Yoon (AIP Advances)
Both site-occupancy and valences of constituent ions are known to play an important role in determining their magnetic phases of spinel ferrite systems. For some manganese-containing ferrites, lattice distortions coming from the Jahn-Teller (JT) effect make it even more complicate to analyze the temperature evolution of the phase. Unlike the previous studies using nanosized samples, in this study, a wide composition range (0 ≤ x ≤ 2 with step of 0.25) of Mn3−xFexO4 powders were prepared by conventional ceramic technique followed by Liquid Nitrogen (LN2) quenching. Subsequently, their structural and magnetic properties have been examined in terms of x by using X-ray diffraction (XRD), vibrating sample magnetometer (VSM), X-ray photoemission spectroscopy (XPS) and Mössbauer spectroscopy. Consequently, we could find out qualitative relation between the Fe content x and the degree of inversion z with an empirical composition formula (Mn1−zFez)[Mn3−x+zFex−z]O4.